Prothèse unicompartimentaire et désostéotomie pour échec d’ostéotomie tibiale : une alternative chirurgicale à l’arthroplastie totale de genouFailed high tibial osteotomy: A joint preserving alternative to total knee arthroplasty - Jones,GG; Clarke,S; Jaere,M; Cobb,JP (Revue de Chirurgie Orthopedique et Traumatologique, 2019)
High tibial osteotomy is an attractive treatment option for young active patients wishing to return to high level activities. However, it is not considered a long-term solution, with 30% revised at ten years. Currently, the only revision option is a total knee arthroplasty, a procedure that might not deliver the functional level expected by these highly active patients. This paper describes a novel joint preserving approach to HTO revision, using assistive technology, in the form of 3D printed guides, to reverse the osteotomy and simultaneously perform a unicompartmental knee replacement. The indications and planning aims for this procedure are discussed, and the preliminary results in four patients presented. Level of evidence: IV.